BIOREMEDIASI TUMPAHAN MINYAK MENTAH DENGAN METODE BIOSTIMULASI NUTRIEN ORGANIK DI LINGKUNGAN PANTAI SURABAYA TIMUR - Munawar Munawar; Mukhtasor Mukhtasor; Tini Surtiningsih (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2007)
The purpose of this paper was to present effects of nutrients in the bioremediation process of spilled crude oil in a coastal environment. An emphasis is directed at looking at effectiveness of organic-based nutrients in that process using a method of bio-stimulation. An insitu test was undertaken in a coastal area, located at the East side of Surabaya City, Indonesia, by making multiple trial compartments, with a size of 0.5 × 0.5 m2 each; and the space between the compartments is 0.25 m. At every compartment, one liter of crude oil was spilled. Three days later, it was added with organic-based nutrient on the treatment (0.2; 0.3 and 0.4 kg/kg soil).